Study of Normal Branching Pattern of the Coeliac Trunk and its Variations Using CT Angiography - Selvaraj, Lakshana (Journal of clinical and diagnostic research, 2015)
Blood vessel anomalies are always interesting from embryological view and of considerable significance from a clinical or a surgical standpoint. Vascular anomalies are usually asymptomatic; they may cause problems in patients undergoing diagnostic angiography or any operative procedure. The length and course of the coeliac artery are variable and its branches frequently arise separately from the main trunk. Several other branches may additionally arise from the coeliac trunk, for example, inferior phrenic arteries, the dorsal pancreatic artery, and the middle colic artery. The present study was undertaken to analyse the vertebral level of origin of coeliac artery, its branching pattern and the associated variations using computed tomographic angiography in 75 subjects. The results obtained were analysed and classified based on Adachi's and Lipshutz's classification method. The results were also compared with various other studies cited in the literature. The level of origin was found to be at the inter-vertebral disc between T12 and L1 in a majority of the cases (70.6%). It was also found that the coeliac trunk trifurcates in majority of the cases i.e. 90.6%. Trifurcation was of two types, classical and non-classical, the classical trunk being the commonest type. Variations included bifurcation of the trunk (8%) with Left gastric artery arising directly from the aorta, in a few cases (1.3%) Common hepatic artery arose as a separate trunk from the aorta. A comprehensive knowledge of this arterial anatomy and variations will be very useful when planning abdominal surgeries and image-guided interventions. The success of procedures such as liver transplantation, intestinal anastomosis, intra-arterial chemotherapy, chemo-embolization, and radio-embolization requires a detailed knowledge of the coeliac artery and its anatomical variants, which are extremely common, to avoid iatrogenic injuries and to prevent complications.